2016
DOI: 10.1186/s13068-016-0653-4
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome de novo sequencing, combined with RNA-Seq analysis, reveals unique genome and physiological features of the amylolytic yeast Saccharomycopsis fibuligera and its interspecies hybrid

Abstract: BackgroundGenomic studies on fungal species with hydrolytic activity have gained increased attention due to their great biotechnological potential for biomass-based biofuel production. The amylolytic yeast Saccharomycopsis fibuligera has served as a good source of enzymes and genes involved in saccharification. Despite its long history of use in food fermentation and bioethanol production, very little is known about the basic physiology and genomic features of S. fibuligera.ResultsWe performed whole-genome (WG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 83 publications
0
48
0
Order By: Relevance
“…BLASTX searches against the nonredundant database at NCBI ( https://blast.ncbi.nlm.nih.gov/Blast.cgi ) generated a further 373 hits. As was observed for S. fibuligera , also S. fodiens lacks genes required for sulfate uptake and assimilation ( 8 ). Running tRNAscan on the scaffolds identified 162 tRNA genes ( 12 ).…”
Section: Genome Announcementmentioning
confidence: 61%
See 1 more Smart Citation
“…BLASTX searches against the nonredundant database at NCBI ( https://blast.ncbi.nlm.nih.gov/Blast.cgi ) generated a further 373 hits. As was observed for S. fibuligera , also S. fodiens lacks genes required for sulfate uptake and assimilation ( 8 ). Running tRNAscan on the scaffolds identified 162 tRNA genes ( 12 ).…”
Section: Genome Announcementmentioning
confidence: 61%
“…Subsequently, S. fibuligera genes encoding these enzymes were used in heterologous hosts, such as Saccharomyces cerevisiae and Yarrowia lipolytica ( 3 7 ). This interest in using S. fibuligera also spurred genome sequencing of this yeast ( 8 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…The role of S. fibuligera as an enzyme producer also spurred interest in using this yeast for bioethanol production ( 3 ). Recently, whole-genome sequencing studies revealed that the genome of S. fibuligera encompasses seven chromosomes with about 18 Mb ( 4 ). Other members of the genus Saccharomycopsis , including S. fermentans , have been described as predacious yeasts that generate penetration pegs with which they kill other fungal cells utilizing prey cell content ( 5 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…Saccharomycopsis species are natural auxotrophs for organic sulfur ( 8 ). In S. fibuligera , the absence of genes involved in sulfate assimilation has been observed ( 4 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…In the yeasts Ogataea polymorpha (Hanson, Byrne, & Wolfe, ; Ravin et al, ), Debaryomyces hansenii (Lynch, Logue, Butler, & Wolfe, ; Marie‐Nelly et al, ), and Saccharomycopsis fubuligera (Choo et al, ), as well as Scheffersomyces stipitis as discussed below, centromeric regions contain clusters of retrotransposons related to S . cerevisiae Ty5.…”
Section: Introductionmentioning
confidence: 99%